2010
DOI: 10.1002/cctc.201000119
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Formic Acid Catalyzed by a Phosphine‐Free Ruthenium Complex in a Task‐Specific Ionic Liquid

Abstract: The dehydrogenation of formic acid is effectively catalyzed by the Ru complex [{RuCl2(p‐cymene)}2] dissolved in the ionic liquid (IL) 1‐(2‐(diethylamino)ethyl)‐3‐methylimidazolium chloride at 80 °C without additional bases. This catalytic system gives TOF values of up to 1540 h−1. Preliminary kinetic insights show formal reaction orders of 0.70(±0.15), 0.78(±0.03) and 2.00(±0.17) for the Ru catalyst, IL 1, and formic acid, respectively. The apparent activation energy of this process is estimated to be (69.1±7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 43 publications
(49 reference statements)
1
35
0
1
Order By: Relevance
“…Therefore, one alternative is chemical hydrogen storage in molecular materials in which the dihydrogen is stored in the form of hydridic and protic hydrogen. Examples are metal hydrides [4][5][6] , ammonia borane derivatives 2,3,7 , formic acid 2,[8][9][10][11][12][13][14][15][16][17] and methanol [18][19][20][21] . Ammonia borane derivatives have a good weight efficiency (r19.4 wt% H 2 ) 2,3,7 , but the solid spentfuels are hardly recyclable.…”
mentioning
confidence: 99%
“…Therefore, one alternative is chemical hydrogen storage in molecular materials in which the dihydrogen is stored in the form of hydridic and protic hydrogen. Examples are metal hydrides [4][5][6] , ammonia borane derivatives 2,3,7 , formic acid 2,[8][9][10][11][12][13][14][15][16][17] and methanol [18][19][20][21] . Ammonia borane derivatives have a good weight efficiency (r19.4 wt% H 2 ) 2,3,7 , but the solid spentfuels are hardly recyclable.…”
mentioning
confidence: 99%
“…To confirm the purity of the released hydrogen we investigated the evolved gas via mass spectrometry of representative samples, which has been applied before [4]. In case of the tested [OAc] À ILs CO 2 and in all experiments diborane (B 2 H 6 ) and ammonia (NH 3 ) are possible co-products.…”
Section: Screening Of Ilsmentioning
confidence: 99%
“…(Boddien et al, 2011;Enthaler et al, 2010;Johnson et al, 2010;Scholten et al, 2010;Tedsree et al, 2011;Yasaka et al, 2010;Zhao et al, 2011) Figure 5. Reversible splitting of formic acid.…”
Section: Formic Acidmentioning
confidence: 99%
“…Structure of amino-functionalized IL 1. Scholten et al, 2010) While the Dupont group reported only about the application of the chloride IL 1, the Shigroup used various anions, i.e. BF4 -, OTf -, NTf2 -and HCOO -.…”
Section: Functionalized Ils For Catalytic Decomposition Of Formic Acidmentioning
confidence: 99%
See 1 more Smart Citation